Facing extreme uncertainty – how the onset of the COVID-19 pandemic influenced product development. Issue 2 (3rd April 2023) - Hölttä-Otto, Katja; Björklund, Tua; Klippert, Monika; Otto, Kevin; Krause, Dieter; Eckert, Claudia; Nespoli, Oscar; Albers, Albert
ABSTRACT: The COVID-19 pandemic has been a global disruption, but little is known about how it impacted product development. Based on interviews of 24 practicing product development leaders, we find that COVID-19 generated a unique combination of external and internal uncertainties and thus had several direct impacts on product development. Initial adaptations were reported in the level of innovation pursued, the development processes and the resourcing. In terms of level of innovation and resourcing, no uniformity in adaptations were observed: opposite changes were made across radical/incremental, expanding/reducing, local/international and internal/external collaboration balances in the different companies' product development activities. Process adaptations were more uniform in direction, focusing on increasing flexibility and agility. In terms of product development methods for different phases, we find companies quickly seeking creative approaches to replace their traditional methods in idea generation, prototyping, customer interaction, validation etc. with virtual means. Furthermore, changes in human interaction quality, particularly informal interaction, were seen to have far-reaching, unintended negative consequences on their creative efforts, whether in product development, development process or resourcing. Overall, the results highlight the diversity of adaptive choices available to respond to external uncertainties, though more research is still needed on how these influence longer term resilience.